STUDI PERSEBARAN BANJIR MENGGUNAKAN SOFTWARE HEC-RAS 2D V6.2 HULU DAS WAY SEKAMPUNG (STUDI KASUS: SUNGAI WAY MINCANG) - Mashuri; M. Gilang Indra Mardika; M. Juang Renaldi Fiqri (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2023)
The Way Mincang River, which is located in Pardasuka District, Pringsewu Regency, Lampung Province, is a periodic river whose flow often overflows during rainy season. The overflow of the Way Mincang River inundated several Pekon in Pardasuka District including the Pekon Tanjung Rusia, Tanjung Rusia Timur, Sukanegeri, Pardasuka and Kedaung. The aim of research to determine the flood discharge with a return period of 10, 25 and 50 years in 2 dimensions with the HEC-RAS v6.2 software, so that the water level and the area of flood-prone distribution in Way Mincang River can be identified. The research location is in Way Mincang Watershed with the downstream of river at coordinates 104.92 BT and -5.50 LS while the upstream of river at coordinates 104.92 BT and -5.57 LS with a river length of 10.29 km, average river width of 15 m-20 m and the study area 2371.34 Ha. The results of analysis show that discharge at periods of 10 years, 25 years and 50 years is 50.29 m3/sec, 63.11 m3/sec and 72.61 m3/sec. The maximum flood water level is 1.88 m in Pekon Pardasuka Timur and the maximum flood area is 0.31 km2 in Pekon Kedaung. Along the Way Mincang watershed is a flood-prone area where the entire pekon (village) is flooded but the coverage area is relatively small, namely <1 km2. This is confirmed by the ratio of total flood inundation and total area of only 5.24%. It is hoped that results of research can be used as a reference for stakeholders in terms of planning and improving Way Mincang Watershed.